2004
DOI: 10.1002/cncr.20398
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma and liver tumors in South African children

Abstract: It appeared from the current results that HCC is more prevalent among children in South Africa compared with the children in more developed countries, although their rates were lower that the rates noted in adults. A collaborative approach will be required to improve their diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 60 publications
3
45
0
Order By: Relevance
“…HCC is one of the most common malignant tumors in China, however, the etiological factors of HCC in China differ from those in the developed countries (Moore et al, 2004). HCC in China is commonly associated with hepatitis B (Zhiqiang et al, 2004), and a large proportion of the HCC patients in China are commonly accompanied by other chronic liver diseases (Cao et al, 2009;Jiang et al, 2009;Lam and Poon, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HCC is one of the most common malignant tumors in China, however, the etiological factors of HCC in China differ from those in the developed countries (Moore et al, 2004). HCC in China is commonly associated with hepatitis B (Zhiqiang et al, 2004), and a large proportion of the HCC patients in China are commonly accompanied by other chronic liver diseases (Cao et al, 2009;Jiang et al, 2009;Lam and Poon, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Criteria of surgical resection for patients with HCC were 1 patients with tumor involving no more than 3 Healey's segments, 2 Child-Turcotte-Pugh (CTP) class A with less than 25% retention of indocyanine green 15 minutes after injection, and 3 no main portal vein trunk involvement or distant metastasis. Liver transplantation was considered in patients fulfilling the Milan criteria with coexisting CTP class B or C cirrhosis.…”
Section: Treatmentmentioning
confidence: 99%
“…Sarcomas are the third most common malignant primary hepatic tumors, comprising approximately 6% of hepatic malignancies in childhood [18]. For example, Moore et al [8] reported 194 cases of malignant primary hepatic tumors in children. Of these patients, 58% had HB, 35% had HCC, and 5% had sarcomas of the liver (including 6 poorly differentiated sarcomas, 2 rhabdomyosarcomas, 1 angiosarcoma, and 1 mesenchymal carcinoma).…”
Section: Discussionmentioning
confidence: 99%